2021
DOI: 10.1002/adfm.202106329
|View full text |Cite
|
Sign up to set email alerts
|

Evolvable Skin Electronics by In Situ and In Operando Adaptation

Abstract: Latest developments in thin-film electronics have put skin electronics in the limelight. Integration of multiple skin sensors and wireless power transferring ability are cardinal components for continuous acquisition of the human signals, enabling higher level of applications in wearable healthcare and AR/ VR devices. Skin sensor is considerably influenced by target body parts and users where it is attached, and thus face various design adjustments for the best performance. However, most skin electronics using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Furthermore, mining more value behind each module , and customizing the functions of modules considering the needs of uses will endow the system with more practical scenarios. , …”
Section: Conclusion and Outlooksmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, mining more value behind each module , and customizing the functions of modules considering the needs of uses will endow the system with more practical scenarios. , …”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Furthermore, mining more value behind each module 57,58 and customizing the functions of modules considering the needs of uses will endow the system with more practical scenarios. 59,60 EXPERIMENTAL SECTION Design and Fabrication of Double-Sided LIG/LIGF. The layout of the specific design of each module in the double-sided wearable multifunctional system has been revealed in the Figure S1.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Secondly, laser-sintered metallic electrode enables a new concept of evolvable skin electronics, of which system’s impedance and functions can be altered during the operation [ 104 ]. The objective of a wearable electronics can be diverse, yet the one of the primary concerns is to measure various physiological data from the body to acquire the current state of the wearer, especially for healthcare purpose.…”
Section: Applicationsmentioning
confidence: 99%
“…( f ) Addition of UV and humidity sensing capabilities by SOA. Reprinted with permission from Ref [ 104 ]. 2022 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, Germany.…”
Section: Figurementioning
confidence: 99%
“…Moreover, the treatment of conductive materials and structures requires some post-processing methods—such as photolithography, ion implantation, thin film deposition, electroplating, UV treatment, etc.—which increases the cost and difficulty of electrode preparation. As a common flexible electrode material, Ag nanomaterials play an important role in many studies, such as 0-dimensional Ag nanoparticles [ 27 , 28 , 29 , 30 ], 1-dimensional Ag nanowires [ 31 , 32 , 33 , 34 , 35 , 36 ], etc. In some studies related to Ag nanomaterial electrodes, it has been found that the contact resistance at junctions between nanomaterials is one of the main issues affecting their electrical conductivity [ 37 ].…”
Section: Introductionmentioning
confidence: 99%